The Impact of Central Bank Monetary Measures on the Czech Mortgage Market - Kamila VESELA (Communications of International Proceedings, 2021)
Mortgage loans have become the dominant financing choice on the market for home loan products in the Czech Republic. The demand for own housing has long been on the rise among the Czech population which goes hand in hand with the demand for mortgage loans. This particular market is affected by a number of factors, one of the key ones being the monetary policy pursued by the Czech National Bank. In recent years, the Czech National Bank has repeatedly introduced monetary policy measures aimed at regulating the amount of money in the economy. In 2020, it proceeded to gradually lower the reference rates on the interbank market with a view to boosting the economy and household consumption inhibited by the Covid-19 pandemic. The presented article aims to evaluate the impacts of monetary measures implemented by the Czech National Bank directed at the Czech loan market, with a particular focus on the Covid-19 period. The study drew on secondary data and data from the Czech Statistical Office, applying mainly time series analyses and regression analyses among others. The research has confirmed the long-standing interest among Czechs in their own housing, as reflected in the stable increase in demand both for residential properties and for home loan products. Despite the decline in economic growth, the loan market continued to expand, experiencing a major upsurge in terms of the number of mortgage loans provided in the second quarter of 2020. The largest increase was seen in loans with over 5-year fixation.
Keywords: Covid-19; mortgage; real estate; rates; market; interest; housing loan